Evaluation of measles vaccination coverage in Lincang City, Yunnan Province, China - Xiaotong Yang; Tingting Tang; Zhikang Yang; Lu Liu; Shuyi Yuan; Tai Zhang (Taylor & Francis Group, 2021)
Background: Lincang City in Yunnan Province on the China-Myanmar border, has reached the World Health Organization recommended coverage (95%) for measles-containing vaccine (MCV), but measles outbreaks still occur. We conducted a survey in Lincang City to determine the measles vaccination status of children on the China-Myanmar border. Methods: We used multistage sampling among children aged 8-83 months. Information on measles vaccination status was obtained from the child's vaccination certificate, and serum samples were tested using commercially available ELISA kits. Results: A total of 938 children were surveyed. The vaccination coverage rate was 98.9% (95% CI: 98.2-99.6%) for measles-containing vaccine dose 1 (MCV1), and 95.8% (95% CI:94.9-96.7%) for measles-containing vaccine dose 2 (MCV2). The timely vaccination coverage rate was 52.0% (95% CI:48.8-55.2%) for MCV1, and 74.1% (95% CI: 82.9-89.0%) for MCV2. The timely-and-complete vaccination coverage rate was 41.0% (95% CI: 36.7-45.3%). The median delay period was 33 (95% CI: 27-39) days for MCV1, and 196 (95% CI: 146-246) days for MCV2. The seropositivity rate in children aged less than 7 years was 94.0% (95% CI: 92.5-95.5%) with a geometric mean titer of 1210.1 mIU/mL. Conclusions: The MCV coverage was high, but timely and timely-and-complete vaccination coverage were low and insufficient to prevent measles outbreaks. It is necessary to add the timely and timely-and-complete vaccination coverage as indicators of vaccination to provide a more complete picture of measles immunization status.